Gestión organizacional de la Empresa “Data Fiber” en la ciudad de Babahoyo periodo 2023. - Vergara Mantuano, José Javier (2024)
The present case study titled "Organizational management of the “Data Fiber” company in the city of Babahoyo, period 2023" has the general objective of evaluating the organizational management in the company by executing research techniques to improve productivity in its operations and thereby way to examine the performance of its processes both internally and externally in order to identify the shortcomings that limit the development of its operations, it also aims to identify the key processes that make up the organizational culture of the entity, seeking to have greater knowledge about the procedures and tactics that are applied, therefore the intention is to propose alternatives that help promote improvement in organizational management. Inductive and descriptive research methods were applied to reinforce the approach to the problem presented, information was collected through research instruments such as the swot matrix and a survey specifically directed in a structured manner towards the company manager. In addition, the theoretical bases were consolidated using various sources from expert authors in management and organizational culture. This is essential for the company, since the development of its activities, strategic decisions and plans focus mainly on productive efficiency, ensuring correct management of its processes, thus allowing it to contribute significantly to the improvement of the operations of the “Data Fiber” organization, achieving greater performance so that it is subsequently directed towards success.